Pengembangan Instrumen Assessment for Learning (AfL) pada Materi Barisan dan Deret - Nasrullah, Nasrullah; Armasari, Fanny (Al Asma: Journal of Islamic Education, 2025)
This study aims to develop an assessment for learning (AfL) instrument on the material of rows and series for students of grade XI SMA that is valid and reliable. The type of research used is Research and Development (R&D), which refers to the instrument development procedure by Djemari Mardhapi. The subjects of this study were all students of class XI UPT SMA Negeri 8 Wajo, consisting of 4 classes with 103 students. The research instruments used were content validity instruments, process assessment instruments, and learning outcomes. The results showed that: (1) The development of assessment for learning (AfL) instruments on the material of ranks and series for grade XI high school students is carried out through the stages of compiling instrument specifications, writing instruments, reviewing instruments, improving instruments, conducting instrument trials, analyzing and assembling instruments; (2) The results of the development of assessment for learning (AfL) instruments on the material of ranks and series for grade XI high school students consist of process and learning outcomes assessment tests, rubrics for assessing cognitive, psychomotor and affective aspects. The assessment for learning (AfL) instrument on the material of ranks and series for students of grade XI SMA has fulfilled the aspects of validity (content validity and construct validity) and reliability.